2017
DOI: 10.1002/ieam.1887
|View full text |Cite
|
Sign up to set email alerts
|

Population-relevant endpoints in the evaluation of endocrine-active substances (EAS) for ecotoxicological hazard and risk assessment

Abstract: For ecotoxicological risk assessment, endocrine disruptors require the establishment of an endocrine mode of action (MoA) with a plausible link to a population‐relevant adverse effect. Current ecotoxicity test methods incorporate mostly apical endpoints although some also include mechanistic endpoints, subcellular‐through‐organ level, which can help establish an endocrine MoA. However, the link between these endpoints and adverse population‐level effects is often unclear. The case studies of endocrine‐active s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 70 publications
0
39
0
Order By: Relevance
“…Finally, issues were identified that aid in distinguishing between endocrineversus nonendocrine-specific responses. These crosscutting issues are broadly outlined below and discussed in detail in the associated companion papers (Coady et al this issue; Marty et al this issue; Mihaich et al this issue; Parrott et al this issue). …”
Section: Crosscutting Issues Relevant To the Evaluation Of Hazards Anmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, issues were identified that aid in distinguishing between endocrineversus nonendocrine-specific responses. These crosscutting issues are broadly outlined below and discussed in detail in the associated companion papers (Coady et al this issue; Marty et al this issue; Mihaich et al this issue; Parrott et al this issue). …”
Section: Crosscutting Issues Relevant To the Evaluation Of Hazards Anmentioning
confidence: 99%
“…This lack of definition is a source of major uncertainty for both hazard and risk assessment. The companion paper by Marty et al. (this issue) used data from the EAS case studies (Supplemental Data S1–S6) to evaluate the population relevance of collected study endpoint data in the context of ecotoxicological hazard and risk assessment for various taxa (invertebrates, fish, amphibians, birds, and mammals).…”
Section: Crosscutting Issues Relevant To the Evaluation Of Hazards Anmentioning
confidence: 99%
See 3 more Smart Citations